Stress Relaxation Behavior of Different Varieties of Potato Tubers Under Compressive Mechanical Loading - Omale, P. A.; Tsanan, J. F.; Salaudeen, O. H.; Olanrewaju, T. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
Potatoes tubers obtain several mechanical injuries during its harvesting, handling and storage and the knowledge of the mechanical properties of potatoes is very important for improving these operations. The stress relaxation of three varieties of Benue State-grown potato tubers was determined using the universal testing machine to study the behavior of the named varieties; orange potato, purple potato and white potato tubers under loading. The potato tubers were cut into cubes of 2700 mm3 and the stress relaxation was observed under the application of compressive force. It was observed that the compressive stress at total relaxation across the three varieties of potato ranged from 0.040-0.071 MPa with orange potato having the highest value of 0.071 MPa while white potato had the least value of 0.040 MPa. The compressive strain at total relaxation for the three varieties of potato tubers ranged from 0.00010 to 0.00011 mm/mm. The compressive load at total relaxation for the three varieties of potato ranged from 15.937 to 28.293 N. The compressive extension at total relaxation for the three varieties of potato tubers ranged from 0.0015 to 0.0020 mm. The load at total relaxation for the three varieties of potato tubers ranged from 15.937 to 28.293 N. Extension at total relaxation for the three varieties of potato tubers ranged from 0.0015 to 0.0020 mm. The maximum compressive stress for the three varieties of potato tubers ranged from 0.133 to 0.188 MPa. The compressive strain at maximum compressive stress for the three varieties of potato tubers ranged from 0.0598 to 0.0601 mm/mm. The compressive load at maximum compressive stress for the three varieties of potato tubers ranged from 53.274 to 75.170 N. The extension at maximum compressive stress for the three varieties of potato tubers ranged from 1.196 to 1.202 mm. Load at maximum compressive stress for the three varieties of potato tubers ranged from 53.27 to 75.17 N. ANOVA and Duncan test at 95% confidence level revealed there was no significant difference across the stress relaxation of the three varieties of potato tubers investigated. The data generated on the three varieties of potatoes indicate that it is safe if the various potatoes varieties are packaged and transported together, and that this will not cause any mechanical damage to the potatoes. It can be concluded that the various varieties of Benue grown potato can use the same post harvest processing and handling machines. These data are also important for maximum efficiency in designing equipment for further processing of potatoes and the reduction of its mechanical damage during postharvest operations such as transportation, packaging and storage of potato tubers.